2010
DOI: 10.1051/0004-6361/201014687
|View full text |Cite
|
Sign up to set email alerts
|

Herschelunveils a puzzling uniformity of distant dusty galaxies

Abstract: The Herschel Space Observatory enables us to accurately measure the bolometric output of starburst galaxies and active galactic nuclei (AGN) by directly sampling the peak of their far-infrared (IR) emission. Here we examine whether the spectral energy distribution (SED) and dust temperature of galaxies have strongly evolved over the last 80% of the age of the Universe. We discuss possible consequences for the determination of starformation rates (SFR) and any evidence for a major change in their star-formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
150
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 32 publications
31
150
0
Order By: Relevance
“…This systematic offset may partly be due to the choice of modified blackbody models fitted by these authors and partly a result of how they selected sources. Indeed, other authors who performed stacking analyses but fitted different models or had different selection criteria, including Pascale et al (2009), Amblard et al (2010, and Elbaz et al (2010), reported higher dust temperatures in alignment with our results. We note that these latter two studies, which are based on galaxy samples selected by Herschel, may be biased in temperature.…”
Section: Evolution Of Dust Temperaturesupporting
confidence: 92%
“…This systematic offset may partly be due to the choice of modified blackbody models fitted by these authors and partly a result of how they selected sources. Indeed, other authors who performed stacking analyses but fitted different models or had different selection criteria, including Pascale et al (2009), Amblard et al (2010, and Elbaz et al (2010), reported higher dust temperatures in alignment with our results. We note that these latter two studies, which are based on galaxy samples selected by Herschel, may be biased in temperature.…”
Section: Evolution Of Dust Temperaturesupporting
confidence: 92%
“…In the redshift range z = 1-3 investigated here, the observed 250 μm fluxes correspond to the peak of the SEDs in the rest frame. As such, the L 250 to L IR correction factors do not vary much as a function of SED shape when compared to using shorter wavelengths (see Figure 3 in Elbaz et al 2010). Indeed, when we compared all of the Chary & Elbaz (2001) SEDs, redshifted to z = 2, the conversion factors were consistent within ≈20%; we also repeated our analysis using the main-sequence SED from Elbaz et al (2011) for all of the bins and found no significant difference.…”
Section: Measuring Average Star Formation Ratesmentioning
confidence: 72%
“…A PREVIEW FOR JWST IR SEDs evolve with redshift, so comparisons must be over similar redshift ranges or must make the necessary adjustments (e.g., Hernán-Caballero et al 2009;Papovich et al 2009;Elbaz et al 2010;Finkelstein et al 2011;Kirkpatrick et al 2012;Rujopakarn et al 2013). We first discuss previous works on this subject; in a following subsection we present results for our demonstration sample of gravitationally lensed, high-redshift galaxies as a case study for galaxies with luminosities and redshifts to be probed with JWST.…”
Section: Application To Distant Galaxiesmentioning
confidence: 99%